Ce nu merge la mașinăriile de creștere urbană din România? Cazul orașelor mici din Nord-Vestul Transilvaniei - Hatos, Adrian (Calitatea Vieții, 2010)
Small Romanian towns have been hit during post-communist transformations by massive loss of human and economic resources due to the vanishing of their industrial economies of reliance. My paper deals with hinders to the necessary planning and completion of actions dedicated to stopping the decline and ignition of durable development in such instances using the framework of urban growth machine and urban growth regimes. First I argue that urban development coalitions can be framed as collective action then I look to several necessary ingredients of it that can explain the (non)emergence or the lack of effectiveness of development coalitions in small Romanian townships. On the basis of non-systematic personal observations from several North-Western Transylvanian small urban settlements I discuss the main obstacles impeding the success of local development coalitions: local myths and the culture of powerlessness, deprived human resources, the actions of anti-development coalitions and defective leadership. Finally I propose that the exit from the vicious circle of anti-development conditions could start from considering the town as a community of practice in which learning should have a great role.